The influence of credits and stigmas in volunteering on depression, the modulating effects of volunteer personality and motivation - Juntao Chen; Yifan Zhang; Suhua Zhou; Chenlu Yang; Lianghua Li; Lu Ma; Shuzhen Zhu (BMC Public Health)
Abstract Depression is a common mental health issue affecting volunteers, which directly impacts the quality of services they provide. This study investigates the unique aspects of volunteer depression and analyzes the roles of volunteer credits, stigmatization, personality traits, and motivations in influencing depression levels. Data were collected from a survey of 822 volunteers from the Red Cross in Hubei Province, China. The results indicate that higher volunteer credits significantly reduced depression scores, while increased stigmatization was associated with higher depression levels. Personality traits such as agreeableness and conscientiousness helped mitigate the negative effects of stigmatization, while openness exacerbated its impact. Furthermore, volunteers driven by understanding and value expression were more susceptible to the adverse effects of stigmatization. The findings highlight the importance of improving volunteer mental health by enhancing team trust and reducing stigmatization. Although the large sample size strengthens the study, the cross-sectional design limits causal inference. Overall, the study underscores the importance of understanding personality traits and motivations in developing effective volunteer support measures, thereby enhancing service quality and community well-being.